Microbial production of hyaluronic acid: current state, challenges, and perspectives - Liu, Long; Liu, Yanfeng; Li, Jianghua; Du, Guocheng; Chen, Jian (Microbial cell factories, 2011)
Hyaluronic acid (HA) is a natural and linear polymer composed of repeating disaccharide units of β-1, 3- N -acetyl glucosamine and β-1, 4-glucuronic acid with a molecular weight up to 6 million Daltons. With excellent viscoelasticity, high moisture retention capacity, and high biocompatibility, HA finds a wide-range of applications in medicine, cosmetics, and nutraceuticals. Traditionally HA was extracted from rooster combs, and now it is mainly produced via streptococcal fermentation. Recently the production of HA via recombinant systems has received increasing interest due to the avoidance of potential toxins. This work summarizes the research history and current commercial market of HA, and then deeply analyzes the current state of microbial production of HA by Streptococcus zooepidemicus and recombinant systems, and finally discusses the challenges facing microbial HA production and proposes several research outlines to meet the challenges.